Enhanced load frequency control: incorporating locational information for temporal enhancement. Issue 10 (5th April 2019) - Syed, Mazheruddin H.; Guillo‐Sansano, Efren; Blair, Steven M.; Burt, Graeme M.; Prostejovsky, Alexander M.; Rikos, Evangelos
Abstract : With the increasing penetration of renewables in power systems, frequency regulation is proving to be a major challenge for system operators using slower conventional generation, and alternative means to provide faster regulation are being actively sought. The participation of demand side management in ancillary service provision is proven in some energy markets, yet its full potential to benefit frequency regulation, including the exploitation of fast power ramping capability of some devices, is still undergoing research. In this study, a novel approach to improve the speed of response of load frequency control, a secondary frequency control approach is proposed. The proposed control is enabled by an effective location identification technique, is highly resilient to anticipated system changes such as reduction of inertia, and enables fully decentralised power system architectures. The effectiveness of the approach is demonstrated and compared to that of present day regulation control, by means of real‐time simulations incorporating appropriate time delays conducted on a five‐area reduced model of the Great Britain power system. The applicability of the method is further proven under realistic communications delays and measurements experimentally using a controller and power hardware‐in‐the‐loop setup, demonstrating its critical support for enabling the stable operation of future power systems.